Black sorghum fodder (Sorghum almum) intake in goats. - Elizondo-Salazar, Jorge Alberto (2004)
During the period of May to December of 2002, in theExperimental Station Alfredo Volio Mata of the University ofCosta Rica, located to an altitude of 1542 elev. and with anaverage annual rainfall of 2050 mm, black sorghum intakewas evaluated in nine La Mancha goats with an average bodyweight of 39 (±2) kg, distributed in a Latin square design 3 x3 repeated. The experimental treatments were the differentages of the forage that is: a) 56, b) 70 and c) 84 days of regrowth.The forage was given in a chopped form (stems andleaves). Each animal received a ration of 5 kg/day. Samplesof offered and rejected material were gathered to analyze drymatter, crude protein and neutral detergent fiber content.Highly significant differences were observed (P<0,01) forfresh forage, dry matter, crude protein and neutral detergentfiber intake by goats according to age of growth. Dry matterintake for the different treatments did not reach the levelsreported in the literature and they were near 1% of bodyweight. Due to the low dry matter intake, crude proteinintake was also low and goats did not fill maintenancerequirements.